ACTIVE VIBRATION CONTROL OF CONTAINER CRANES AGAINST EARTHQUAKE INDUCED VIBRATION - Azeloglu, C. Oktay; Sagirli, Ahmet (YILDIZ TECHNICAL UNIV, 2011)
This paper is concerned with the active vibration control of container cranes against earthquake induced vibration. To accomplish this purpose, firstly a multi degree-of-freedom nonlinear dynamic model is developed including behavior of the container cranes under earthquakes and dynamics of soil and linear motors and then a Self-tuning Fuzzy Logic Controller (STFLC) is designed to reduce the vibrations of the crane structure. Vibration control using intelligent controllers, such as fuzzy logic has attracted the attention of structural control engineers during the last few years, because fuzzy logic can handle, uncertainties and heuristic knowledge and even non-linearities effectively and easily. The improved seismic control performance can be achieved by converting a simply designed static gain into a real time variable dynamic gain through a self-tuning mechanism. Performance of the designed STFLC and active vibration control system is simulated. The time history of ground motion of the Kobe earthquake (M-w=7,2) in 1995, which is a disturbance input, is applied to modeled container crane. Simulation results exhibit that superior earthquake induced vibration suppression is achieved by the use of designed controllers and active vibration control system. It is seen that this controller descends the effects of such accelerations substantially. It can be concluded that the controllers used may affect the structural design of cranes drastically and improves safety of cranes.
Keywords: Self-tuning fuzzy logic control; container cranes; nonlinear dynamic modeling; active vibration control; earthquake-induced vibration; Engineering